2022
DOI: 10.1021/acs.nanolett.2c03383
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoplasmonics beyond Metals: Ultrahigh Sensing Performance in Transparent Conductive Oxide Nanocrystals

Abstract: Active modulation of the plasmonic response is at the forefront of today's research in nano-optics. For a fast and reversible modulation, external magnetic fields are among the most promising approaches. However, fundamental limitations of metals hamper the applicability of magnetoplasmonics in real-life active devices. While improved magnetic modulation is achievable using ferromagnetic or ferromagnetic-noble metal hybrid nanostructures, these suffer from severely broadened plasmonic response, ultimately decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…In such an effect, the non-diagonal elements of the dielectric tensor of the magnetized ferromagnetic material result in the coupling between two orthogonal polarizations of the optical signal, and the intensity change of the reflectance or transmittance under transverse magnetization. Previously, MOKE has consistently demonstrated superiority in applications with various scopes, such as biosensing, 8–10 optical isolation 7 and modulation, 3,11,12 and data storage. 6 In accordance with the magnetic field direction, MOKEs can typically be categorized into three types: polar MOKEs, in which the direction of magnetization is perpendicular to the sample surface; longitudinal MOKEs, in which the direction of magnetization is parallel to the incident surface and sample surface; and transverse MOKEs (T-MOKEs).…”
Section: Introductionmentioning
confidence: 99%
“…In such an effect, the non-diagonal elements of the dielectric tensor of the magnetized ferromagnetic material result in the coupling between two orthogonal polarizations of the optical signal, and the intensity change of the reflectance or transmittance under transverse magnetization. Previously, MOKE has consistently demonstrated superiority in applications with various scopes, such as biosensing, 8–10 optical isolation 7 and modulation, 3,11,12 and data storage. 6 In accordance with the magnetic field direction, MOKEs can typically be categorized into three types: polar MOKEs, in which the direction of magnetization is perpendicular to the sample surface; longitudinal MOKEs, in which the direction of magnetization is parallel to the incident surface and sample surface; and transverse MOKEs (T-MOKEs).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] During the recent decades, much research effort has been devoted to endowing chirality to metallic nanomaterials, with the aim to explore their strong light-matter interactions. [30][31][32][33][34][35] The combination of chirality and magnetism in magnetic oxide nanomaterials (MONs) provides chiral MONs (CMONs) with novel functionalities and potential applications as shown in Figure 1. [36][37][38][39][40] The electromagnetic properties of chiral materials have been investigated under a static magnetic field by manipulating the interaction behaviors with light.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from that, some recent advances of nonconventional materials for magneto-plasmonics include transparent oxide nanoparticles and ferromagnetic Ni nanodisks. , Hartstein et al used magnetic circular dichroism (MCD) spectroscopy and probed the infrared localized surface plasmon resonances of p-Cu 2– x Se, ZnO, and tin-doped In 2 O 3 nanocrystals to quantify the effective carrier masses ( m *) . Gabbani et al reported the highest magneto-plasmonic performance of transparent conductive oxide nanocrystals, such as F- and In-codoped CdO, which are considered as nonmagnetic plasmonic materials . Maccaferri et al demonstrated that the phase of localized plasmon resonances excited the transverse electric field, and spin–orbit coupling plays an active role on the magneto-optics response of the ferromagnetic Ni nanodisks .…”
Section: Introductionmentioning
confidence: 99%